X^3 - x^2 - 2x = 0
x ( x^2 - x - 2 ) = 0
x (x-2) (x+1) = 0
x = 0
x-2 = 0 --> x = 2
x+1 = 0 --> x = -1
x = 0, x = 2, x = -1
You do pemdas and the answer should be 27
Answer:4
Step-by-step explanation:
X= 2
3x= 3×2
3×2=6
6-2=4
soh cah toa
that is the saying I use
we will use cah
c is cos
a is ajacent
h is hypotinuse
to find cos K we need to do
adjacent / hypotenuse
can you do that and write it in the comments
1.)
Between year 0 and year 1, we went from $50 to $55.
$55/$50 = 1.1
The price increased by 10% from year 0 to year 1.
Between year 2 and year 1, we went from $55 to $60.50.
$60.50/$55 = 1.1
The price also increased by 10% from year 1 to year 2. If we investigate this for each year, we will see that the price increases consistently by 10% every year.
The sequence can be written as an = 50·(1.1)ⁿ
2.) To determine the price in year 6, we can use the sequence formula we established already.
a6 = 50·(1.1)⁶ = $88.58
The price of the tickets in year 6 will be $88.58.